Mahasiswa KUKERTA UNRI 2022 Melaksanakan Gebyar Muharram di Desa Marsawa Kuantan Singingi - Ashaluddin Jalil; Akbar Muhammad Fadli; Atika Anggraini; Aulia Fatmawati; Harsilaningsih Harsilaningsih; Oktagina Feronica; Muhammad Arifin; Muhammad Fandi; Rati Rahayu; Sigit Muamar Yusuf; Wulan Cahyati (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The turn of the Hijri New Year on 1 Muharram is an important moment for Muslims. Children have a very important role in ensuring the existence of the nation and state in the future. The purpose of this study is to find out how effective Gebyar Muharram's activities are to understand deeply in increasing religious knowledge. This research uses a community empowerment-based method of what?only the problems, advantages, and needs of the community. The approach used is to use a scientific point of view education, especially religious knowledge. Results This study shows that the activities of Gebyar Muharram have an effect on significantly with the competition, children become more enthusiasm and interest in learning Islam.